Formation and Essence of Turkey's Security Strategy (American Journal of Public Diplomacy and International Studies (2993-2157), 2025)
The purpose of this study is to analyze the latest developments in Turkey's defense and security policy. The events of the "Arab Spring" have caused many political changes in the Middle East region and radically changed Turkey's security strategy. The study highlights the main driving forces, goals and principles of Turkey's policy aimed at expanding its influence in the international arena as a regional player, increasing its ability to combat threats and strengthening its military potential. It also analyzes in detail the external and internal factors underlying this strategy.